Study of the plant biodiversity at Najran, Alswayda, Syria (Damascus University Journal of agriculture sciences, 2025)
The research was carried out in the Najran region, As-Suwayda Governorate (800 meters altitude), during the period between December 2020 and June 2021, with the aim of determining the wild plant species spread in the study area and their degree of spread, in addition to studying the effect of seed depth in soil on the average germination of seeds spotted golden thistle Scolymus maculatus is one of the most common species in the study area.Through the study, 42 plant species belonging to 22 plant families were identified, including ten species of the compound family Asteraceae, and the spread of these species was between medium and common, except for some species that were rare in spread, namely: Yellow Asphodel Asphodeline brevicaulis,Isatis Isatis lusitanica,  Ornithogalum reticulatum, rock phagnalon Phagnalon rupestre, blackberry nightshade Solanum nigrum, and Horizontal navelwort Umbilicus horizontalis.By comparing the results of this study with the flora of Syria and Lebanon and the available atlases, it was found that there are plant species spread in Najran. However, their spread was mentioned within the Syrian flora in some Syrian governorates, but they were not mentioned in Jabal al-Arab, namely: Scarlet Pimpernel Anagallis arvensis, Italian bugloss Anchusa italica, madwort Asperugo procumbens, Iberian star-thistle Centaurea iberica, goose foots Chenopodium album,horse weed Conyza ambigua sweet clover Melilotus indicus, grape hyacinths Muscari racemosum, narrowleaf plantain Plantago lanceolata, milk thistle Silybum marianum, Glandular SpeedwellVeronica cymbalaria. It was also mentioned that the species horizontal navelwort Umbilicus horizontalis spreads in Lebanon only and was not mentioned in Syria within the the flora, in addition to mentioning the spread of the two species Phagnalon rupestre and spotted golden thistle Scolymus maculatus in the Syrian flora The Syrian governorates, including As-Suwayda, but they were not mentioned in any of the available atlases.The experiment that was carried out in pots on Scolymus maculatus seeds also showed that the average germination increases with increasing depth of seeds under the soil surface.
Keywords: wild plant species; degree of spread; seed depth; average of germination; flora